Addition of Ceftriaxone and Amikacin to a Ciprofloxacin plus Metronidazole Regimen for Preventing Infectious Complications of Transrectal Ultrasound-Guided Prostate Biopsy: A Randomized Controlled Trial - Mohammad-Hossein Izadpanahi; Kia Nouri-Mahdavi; Seyed Mahmood Majidi; Mohammad-Hatef Khorrami; Farshid Alizadeh; Mehrdad Mohammadi-Sichani (Advances in Urology)
Background. The objective of this study was to evaluate the efficacy of adding single doses of ceftriaxone and amikacin to a ciprofloxacin plus metronidazole regimen on the reduction of infectious complications following transrectal ultrasound-guided prostate biopsy (TRUS Bx). Materials and Methods. Four hundred and fifty patients who were candidates for TRUS Bx were divided into two groups of 225 each. The control group received ciprofloxacin 500 mg orally every 12 hours together with metronidazole 500 mg orally every 8 hours from the day prior to the procedure until the fifth postoperative day. In the second group, single doses of ceftriaxone 1 g by intravenous infusion and amikacin 5 mg/kg intramuscularly were administered 30–60 minutes before TRUS Bx in addition to the oral antimicrobials described for group 1. The incidence of infection was compared between the groups. Results. The incidence of infectious complications in the intervention group was significantly lower than that in the control group (4.6% versus 0.9%, p=0.017). Conclusion. The addition of single doses of intramuscular amikacin and intravenously infused ceftriaxone to our prophylactic regimen of ciprofloxacin plus metronidazole resulted in a statistically significant reduction of infectious complications following TRUS Bx.